Awareness and Patronage of Healthcare Professional Indemnity Insurance: Empirical Evidence among Medical Practitioners in Lagos, Nigeria: Array - Ajemunibohun, Sunday (Acta Universitatis Danubius. Œconomica, 2020)
Healthcare Professional indemnity insurance (HPII), otherwise known as medical malpractice insurance or medical errors and omission insurance, is a legal liability insurance that helps rescue the medical practitioners from medical liability lawsuits or negligence that may be brought forward by a patient. It is thus fundamental for managing liability risks that may ensue from the activities of medical practitioners such as surgeons, physicians, dentists, pharmacists, opticians, nurses, physiotherapists and the likes. The thrust of the study, therefore, is to investigate the awareness level and extent of patronage among medical practitioners regarding professional indemnity insurance policy in Nigeria. This study adopted descriptive research design with the help of a survey approach. While judgmental sampling technique was adopted for information selection, a questionnaire was used for data collection. Two hundred fifty (250) medical practitioners that participated in the study were drawn from five (5) divisional areas in Lagos State, which is the population of the study. Two (2) hypothetical statements were tested with statistical intervention of Kolmogorov-Smirnov test and Kendall’s tau Correlation technique. It was found out that the level of awareness of healthcare professional indemnity insurance policy is low among the operators of private health facilities in the studied areas. Thus, extent of patronage of PII is low among the operators of private health facilities in the studied areas, and by implication, the extent of patronage of PII is low among the operators of private health facilities in Nigeria. The study recommends that the Nigerian Medical Association (NMA) should advocate Healthcare Professional Indemnity Insurance policy among its members so as to help improve awareness level of this insurance protection. The state can also promote this indemnity insurance awareness as a medical liability risk management technique through the instrumentality of law.